Benign prostate obstruction in the primary care setting: A Case Report and Review - Roy Andrew Halim Liem; Aulia Rahman Putra (Department of Urology, Faculty of Medicine, Universitas Brawijaya, 2023)
Introduction. Benign prostatic hyperplasia is a prevalent issue among the elderly. The prevalence continues to rise every year and disrupts the patient's quality of life. It is often observed that individuals with this disease frequently exhibit lower urinary tract symptoms (LUTS) due to bladder outlet obstruction (BOO). The case was reported at Tanjung Kasuari Community Health Centre, Sorong City, West Papua, Indonesia.Case. An elderly male, 69 years old, came with complaints of highly frequent night urination (nocturia), experienced a weak urine flow, and difficulty postponing urination (urgency). The patient was treated with empirical therapy of Oral Tamsulosin 0.4mg once daily for 2 weeks and lifestyle modifications.Conclusion. Primary care physicians play an important role in early detection, predominantly in remote locations, but in complex cases when a more precise diagnosis and further management is necessary, consider referring immediately to urologists.